Evaluate :
Give your answer correct to 4 decimal places .
Note
Euler- Mascheroni Constant ( ) 0.57721 Take this value for the question .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First let us substitute x 1 2 8 = u
So we get 1 2 8 1 ∫ 0 ∞ ( u ( e − u − 1 + u 2 1 ) ) d u
Let us forget about the 1 2 8 1 part now and concentrate on the integral itself.
Let us write the integral in the limit form.
t → 0 + , X → ∞ lim ∫ t X ( u e − u − u 2 ( u 2 + 1 ) u ) d u
We know :-
∫ u 2 ( u 2 + 1 ) u d u = 2 1 ∫ z ( 1 + z ) d z = 2 1 ( ln ( z ) − ln ( z + 1 ) ) = 2 1 ( ln ( u 2 ) − ln ( u 2 + 1 ) ) (without the integration constant)
Applying by parts to the first integral we have:-
t → 0 + , X → ∞ lim ( e − X ln ( X ) − e − t ln ( t ) + ∫ t X e − z ln ( z ) d z + 2 1 ( ln ( t 2 ) − ln ( t 2 + 1 ) − ln ( X 2 ) + ln ( X 2 + 1 ) ) )
= t → 0 + , X → ∞ lim ( e − X ln ( X ) − e − t ln ( t ) + ln ( t ) + ∫ t X e − z ln ( z ) d z + 2 1 ( − ln ( t 2 + 1 ) − ln ( X 2 ) + ln ( X 2 + 1 ) ) )
= t → 0 + , X → ∞ lim ( e − X ln ( X ) + ( 1 − e − t ) ln ( t ) + ∫ t X e − z ln ( z ) d z + 2 1 ( − ln ( t 2 + 1 ) + ln ( X 2 X 2 + 1 ) ) )
Now let us evaluate the limits one by one :-
Limit 1:- X → ∞ lim e − X ln ( X ) = 0
Limit 2:- t → 0 + lim ( 1 − e − t ) ln ( t ) = t → 0 + lim t ln ( t ) ⋅ t 1 − e − t = 0
Because t → 0 + lim t ln ( t ) = 0 and t → 0 + lim t 1 − e − t = 1
Limit 3:- t → 0 + lim ln ( t 2 + 1 ) = ln ( 1 ) = 0
Limit 4:- X → ∞ lim ln ( X 2 X 2 + 1 ) = ln ( 1 ) = 0
I'll leave it upto the readers to prove the limits 1 to 4 . They are pretty elementary and should be easy to prove using taylor series or L'Hopital .
So we have only one limit left and it is
t → 0 + , X → ∞ lim ∫ t X e − z ln ( z ) d z = Γ ′ ( 1 ) = Γ ( 1 ) ψ ( 1 ) = ψ ( 1 ) = − γ = − 0 . 5 7 7 2 1
Here Γ ( x ) denotes the Gamma Function and Γ ′ ( x ) denotes it's derivative wrt x and ψ ( x ) denotes the Digamma Function .
The integral ∫ 0 ∞ e − z ln ( z ) d z is a well known integral . Here is a great youtube video by Dr.Peyam evaluating this integral. Dr.Peyam integral video .
So our answer is :- 1 2 8 − γ = − 0 . 0 0 4 5